PEMANFAATAN VIDEO PENDEK TIKTOK/CAPCUT SEBAGAI MEDIA PEMBELAJARAN INOVATIF DI SMA NEGERI 6 PEMATANGSIANTAR - Alfrido Jaya Siahaan; Ester Enjelina Pasaribu; Sarah Priscilla Silitonga; Daniel Saputra Gurning; Jeini Fitriani Purba; David Berthony Manalu; Binsar Tison Gultom (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The integration of digital technology in education has encouraged the use of innovative learning media that align with students’ characteristics. Social media platforms such as TikTok, supported by video editing applications like CapCut, have the potential to be utilized as short video-based learning media. This community service activity aimed to enhance students’ understanding and skills in creating short instructional videos using TikTok and CapCut. The activity was conducted on December 8, 2025, involving 36 students of SMA Negeri 6 Pematangsiantar as community service partners. The implementation method employed training activities consisting of material presentation, hands-on practice in producing instructional videos, and evaluation of the learning outcomes. The results indicated that students were able to produce short instructional videos creatively and demonstrated improved understanding of learning materials and the educational use of digital media. This activity contributed positively to fostering innovative, creative, and technology-based learning practices that support student engagement and learning effectiveness in the school environment. The activity also encouraged collaboration among students, enhancing their communication and teamwork skills. Feedback collected from participants highlighted increased confidence in using digital tools for educational purposes. Future initiatives will focus on expanding this program to include more schools and diverse digital media platforms. The program’s success underscores the importance of integrating digital literacy into the curriculum to prepare students for future academic and professional environments. Additionally, educators reported that the initiative enhanced their teaching strategies by incorporating more interactive and student-centered approaches. Ongoing assessment and feedback will guide the refinement and scalability of the program to maximize its impact across different educational contexts.